2014
DOI: 10.1063/1.4895215
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stability of red palm oils blended chicken nuggets during frozen storage

Abstract: Abstract. The effects of red palm oils known as Naturally Vitamin Rich Oil (NVRO) on the lipid stability of chicken nuggets were determined. Lipid oxidation was analyzed during frozen storage (-18 °C) for up to 4 months. Thiobarbituric acid (TBA) values and peroxide value (PV) for all samples chicken nuggets increased throughout 3 months of frozen storage and then start to decrease thereafter. Chicken nuggets formulated with NVRO, NVRO-100 and NVRO-50 showed lower TBA values and PV compared to the samples prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
1
6
1
1
Order By: Relevance
“…This may be due to the high antioxidant source from carotenoid compound that can slow down the formation of peroxide (Nagendran, Unnithan, Choo, & Sundram, 2000). The result is similar with Kamaruzaman, Babji, Ismail, and Peng (2015)work on chicken nugget samples blended with red palm oils has significantly ( p < .05) lower peroxide value. For MCS, the peroxide value increases significantly ( p < .05) after 24 hr of oxidative test.…”
Section: Resultssupporting
confidence: 89%
“…This may be due to the high antioxidant source from carotenoid compound that can slow down the formation of peroxide (Nagendran, Unnithan, Choo, & Sundram, 2000). The result is similar with Kamaruzaman, Babji, Ismail, and Peng (2015)work on chicken nugget samples blended with red palm oils has significantly ( p < .05) lower peroxide value. For MCS, the peroxide value increases significantly ( p < .05) after 24 hr of oxidative test.…”
Section: Resultssupporting
confidence: 89%
“…This showed that the degradation of the Vitamin E homologs was at a similar rate. This is unlike the findings by Kamaruzaman 2015 for red palm olein in blended chicken nuggets and Yi et al, for palm olein/fish oils where they found faster degradation of αtocopherol and α-tocotrienols 43,44 . This seems to show that Vitamin E homologs degradation may be different in its original form than when it is processed with other food/oil components.…”
Section: Phytonutrients Contentcontrasting
confidence: 89%
“…Our findings are in contrast with the results of previous research possibly due to the decomposition of rosemary and other water-soluble anti-oxidants during deep frying ( 36 ). Kamaruzaman et al ( 37 ) reported that red palm oil has a high oxidative stability and contains high levels of fat-soluble anti-oxidants, such as vitamin E and carotenoids. The content of β-carotene after the 10th frying session was the highest in the red palm oil (143 mg kg −1 ).…”
Section: Resultsmentioning
confidence: 99%